2016
DOI: 10.1002/etc.3507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on acute toxicity of cadmium, copper, nickel, and zinc in individual‐metal exposures to Daphnia magna neonates

Abstract: In previous studies, variability was high among replicate acute cadmium (Cd) Daphnia magna lethality tests (e.g., >10-fold range of median effect concentrations [EC50s]), less among zinc (Zn) tests, and relatively low for copper (Cu) and nickel (Ni) tests. Although the US Environmental Protection Agency’s (USEPA’s) protocol includes starting toxicity tests with neonates less than 24 h old, the authors hypothesized that age-related differences in sensitivity to metals might occur even within that relatively nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 16 publications
(30 reference statements)
0
18
0
1
Order By: Relevance
“…We also found that very high concentration of DFO caused some mortality in the early stage of Daphnia culture. High excessive concentration of oligosaccharide would affect the osmoregulation of Daphnia at an early stage because the early‐life stages of aquatic animals are the most sensitive stage in their life cycles (Bianchini & Wood, ; Noonak & Peerakietkhajorn, ; Traudt, Ranville, & Meyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that very high concentration of DFO caused some mortality in the early stage of Daphnia culture. High excessive concentration of oligosaccharide would affect the osmoregulation of Daphnia at an early stage because the early‐life stages of aquatic animals are the most sensitive stage in their life cycles (Bianchini & Wood, ; Noonak & Peerakietkhajorn, ; Traudt, Ranville, & Meyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because organisms of different developmental stages may differ in their sensitivity to a chemical, many regulatory agencies (USEPA 2002;OECD 2004) specify that acute toxicity tests should be started with D. magna younger than 1 day old. However, we have observed relatively high variability in the toxicity of Cd and Zn to D. magna neonates Traudt et al 2015) and have demonstrated that this variablity is at least partly caused by major changes in sensitivity to the metals even within their first day postbirth (Traudt et al 2016). This methodologically induced variability can have important consequences, especially for predictions of metal-mixture toxicity when using results from individual-metal tests.…”
mentioning
confidence: 84%
“…Those EC50 values, slopes, and their standard errors were calculated from results of the individual-metal toxicity tests conducted concurrently with each ternary-metal toxicity test. Due to high age-dependent variability of EC50 values for D. magna neonates exposed to some of these metals, 18 it was important to calculate the predicted toxicity based on the individual-metal tests that had been conducted on the same day as a given mixture test (instead of consolidating all of the individual-metal data to obtain a central-tendency concentration–response curve for each metal).…”
Section: Methodsmentioning
confidence: 99%